Flow and heat transfer measurements in natural convection in coarse-grained porous media. (March 2019) - Ataei-Dadavi, Iman; Chakkingal, Manu; Kenjeres, Sasa; Kleijn, Chris R.; Tummers, Mark J.
Highlights: Two observed heat transfer regimes: reduced heat transfer regime at lower Rayleigh numbers, asymptotic regime at higher Rayleigh numbers. Convective heat transfer for all sphere conductivities, sizes, and packings converge to the curve for Rayleigh-Bénard convection. In the asymptotic regime, the flow penetrates into the porous layer leading to much higher velocity in the core region. The comparison between thermal length scales and porous length scales determines the flow structure and heat transfer in porous media. Abstract: This paper reports on an experimental study of natural convection in an enclosure that is heated at the bottom and cooled at the top, filled with a packed bed of relatively large solid spheres. Nusselt numbers were measured for various sphere conductivities, spheres sizes and sphere packings for Rayleigh numbers varying between 10 7 and 10 9 . The Nusselt number measurements showed that at lower Rayleigh numbers, the heat transfer is lower than that for pure Rayleigh-Bénard convection, with the difference depending on packing type, size, and conductivity of the spheres. However, at high Rayleigh numbers, there exists an asymptotic regime where the convective contribution of the total heat transfer for all sphere conductivities, sizes, and packing types collapse on a single curve which is very close to the curve for pure Rayleigh-Bénard convection. Refractive index-matching of the fluid and the solid spheres enabled the use of particle image velocimetry and liquid crystal thermography to obtain highly resolved velocity and temperature fields. The comparison of the velocity and temperature fields for the two heat transfer regimes showed that the velocity magnitudes inside the pores in the core region are much higher in the asymptotic regime than those in the low Rayleigh number regime, which lead to a deeper penetration of cold and hot fluid elements and higher heat transfer.